2018
DOI: 10.1177/0734242x18755894
|View full text |Cite
|
Sign up to set email alerts
|

A multi-criteria decision-making approach to rank supplier selection criteria for hospital waste management: A case from Pakistan

Abstract: To address environmental issues and cost effectiveness, waste management is necessary for healthcare facilities. Most importantly, segregation of hazardous and non-hazardous waste must be done as in many developing countries; disposal of both types of healthcare waste is done together, which is an unsafe practice. Waste generated in hospitals needs proper management to minimise hazards for patient and healthcare workers. At the same time, it is quite difficult for hospitals to find a systematic way to select a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 24 publications
(16 reference statements)
0
16
0
6
Order By: Relevance
“…Data from the World Health Organization indicate that the rate of HCW generation varies depending on the country and the type of activity developed by the waste facility (WHO, 2014). In a Pakistan study, infectious waste of consultation clinics was around for 8% of the total generated (Ishtiaq et al, 2018). In the USA, hazardous waste represented 26.1%, 24.7% and 14.7% of all HCW generated in hospitals, laboratories and veterinary clinics, respectively (WHO, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the World Health Organization indicate that the rate of HCW generation varies depending on the country and the type of activity developed by the waste facility (WHO, 2014). In a Pakistan study, infectious waste of consultation clinics was around for 8% of the total generated (Ishtiaq et al, 2018). In the USA, hazardous waste represented 26.1%, 24.7% and 14.7% of all HCW generated in hospitals, laboratories and veterinary clinics, respectively (WHO, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ishtiaq et al (2018) pointed out that in developing countries there is a lack of regulations and rules for management of effective and efficient hospital waste, which represents a problem to correct management of wastes by health services. Waste segregation is one of most important criteria selected by health workers, emphasizing the relevancy of the segregation (Ishtiaq et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Determine multiple typical C&DW utilization modes in Xi'an, China C&DW utilization modes are essentially combined technologies of crushing and recycling. Before C&DW is recycled and reused, it needs to be crushed by the strong external force generated by the crusher (Ishtiaq et al, 2018). The crushing of C&DW can be done either on the construction site or subcontracted to others after being transported to specified sites.…”
Section: Phase 1: Construct the Canddw Utilization Mode Evaluation Matrixmentioning
confidence: 99%
“…The difference in the results was attributed to the effect of the difference in the cost-based concerns of managers and regulation-oriented concerns of government officials, on the experts that completed the surveys (Ho, 2011). A similar work was performed by Ishtiaq et al (2018) in Karachi, the biggest province of Pakistan, for selection of hospital MWM service suppliers. In this research, waste management costs and service supplier selection were found to be the two most important criteria at 45.5% and 31.5%, respectively.…”
Section: Literature Surveymentioning
confidence: 99%